Behavioural economics vs social practice theory: Perspectives from inside the United Kingdom government. (December 2018) - Hampton, Sam; Adams, Rob
Highlights: This paper presents exploratory evidence from interviews with a selection of UK Government Social Researchers (GSRs) working on energy and climate. It offers their perspectives on the intellectual standoff between behavioural economics and practice theory within energy research. These GSRs actively engage with social theory and there is an appetite for policy relevant energy research using practice theory. There is a need for an evidence base for practice-inspired policy instruments: GSRs could help to develop this. Abstract: This paper contributes to the ongoing debate on the role of the social sciences in influencing energy and environmental policy. It presents the views of research professionals inside government on the apparent stand-off between proponents of behavioural economics and adopters of social practice theory in academic energy research. Drawing on auto-ethnographic insights and interviews with government social researchers (GSRs) working on energy and climate change, we chart the rise of behavioural economics within the UK government, discussing the reasons behind its success, and its limitations. GSRs' perspectives on energy research using practice theory are presented, juxtaposed with arguments which help to explain why policy engagement is not a ubiquitous ambition for all energy researchers. We find that government social researchers actively engage with a range of theoretical approaches and social scientific methods. They express enthusiastic interest in research using practice theory, but point to a need for applicable evidence if they are to use it in their own practice. Applying insights from the two theories themselves, we tentatively suggest ways in which GSRs could help, and be helped, to incorporate practice theory into mainstream policy discourse.